Analysis and Fabrication of Fused Fiber Optic Couplers for Communication Systems - Shaari, Ahmad Zaki (2006)
Optical couplers such as fused optical fiber coupler are widely used in the network communication systems as either splitters or combiners. There are not much of theories available to describe the core and cladding interaction model inside fused coupler's region. In this study, suitable Models for analysis of core to cladding guidance interaction using BPM-CAD simulation are created. While core guidance occurs in between core ratios 1 to 0.65, cladding guidance does support propagation at certain core ratio lower than 0.65 with slightly different results between various Models. The Models are also able to generate low excess losses in both the simulated core guidance and cladding guidance. Excess loss in real fused couplers depends on their elongations, which can be controlled through certain set-up parameters such as torch head positions and motor speed. The effects of changing hydrogen flowrate and torch head positions do not have direct relationship with the insertion loss of WDM coupler, hence scientifically, the conclusion of fusion temperature effect on coupling cannot be made. Some design parameters are found out to confirm quite well with the parameters found from fabrication. This has been demonstrated through theoretical pulling signatures for various fused couplers. Besides examining 1 x 2 fused couplers, the study on triangular shape arrangement of 1 x 3 monolithic star couplers do indicate that equal couplings in all output ports are possible if correct Intertwined Method of twisting fibers is used. The same technology used in fabricating fused coupler, is used to fabricate lattice filter, which has channel spacing 2.84 nm or 178 GHz. Generally, all the studies are carried out at most levels including theory, simulation and experiment. These findings or data are analyzed to show the relationship between them and they are also discussed in details in this thesis